The Effect of Tourist Attraction on Revisit Decisions with Visiting Interest as an Intervening Variable (Case Study: Punti Kayu Nature Park in Palembang) - Anggraini, Meisya; Putri, Vania Okky; Simangunsong, Kartika Theresia; Priyanto, Wisanggeni Agus (International Journal of Sustainable Competitiveness on Tourism, 2025)
Abstract This research is motivated by the decrease of attraction of the Taman Alam Punti Kayu Nature Park which is the only natural tourist attraction in Palembang City. The study aims to determine the effect of tourist attraction on revisit decision with a visiting interest as intervening variables. Based on initial observations that have been made at Punti Kayu Nature Park Palembang, the attraction component is quite adequate for the accessibility, amenities, attractions, and other public facilities. The study included 95 individuals who visited the Punti Kayu Nature Park. The analysis of data used in this research is descriptive and quantitative, and uses the structural technique Equation Modeling (SEM-PLS) Version 3.0. to test the relationship between variables. The findings of the study are divided into two stages, an outer model evaluation that tests the validity and reliability of research data, and an inner model evaluation that tests the practicality of research instruments. Research findings indicate that variable appeal significantly affects revisit decisions and visiting interests. Subsequently, the interest in visiting has had a significant impact in mediating the appeal of tourist attraction and revisit decisions. Keywords: Tourits Attraction; Revisit Decision; Visiting Interest.